Analysis of Clinical Rehabilitation of Ischemic Stroke - Zhouting FU; Wei TANG (康复学报)
The intervention time of clinical early rehabilitation, and the clinical curative effect of different rehabilitation approaches on acute ischemic stroke were summarized and analyzed. The results showed that early rehabilitation nursing, early nerve repair and early cognitive training can effectively improve the rehabilitation level of patients, and reduce the complications. In the restoration process of patients during the recovery, applying rehabilitation techniques such as exercise relearn, mandatory exercise therapy, robot assisted exercise therapy, motor imaging therapy, etc., combined with acupuncture could obtain good effects, which suggested that modern rehabilitation techniques and traditional rehabilitation techniques should be combined in order to provide better diagnosis and treatment services for patients with cerebral ischemic stroke.